2019
DOI: 10.3390/nu11040745
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns, Skeletal Muscle Health, and Sarcopenia in Older Adults

Abstract: In recent decades, the significance of diet and dietary patterns (DPs) for skeletal muscle health has been gaining attention in ageing and nutritional research. Sarcopenia, a muscle disease characterised by low muscle strength, mass, and function is associated with an increased risk of functional decline, frailty, hospitalization, and death. The prevalence of sarcopenia increases with age and leads to high personal, social, and economic costs. Finding adequate nutritional measures to maintain muscle health, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
154
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(159 citation statements)
references
References 173 publications
(407 reference statements)
1
154
0
4
Order By: Relevance
“…Several systematic reviews and meta-analyses showed that adherence to a Mediterranean diet is associated with reduced risk of frailty, incident frailty, cognitive decline, mild cognitive impairment, Alzheimer's disease, and progression from mild cognitive impairment to Alzheimer's disease (131)(132)(133)(134)(135). A recent systematic review also showed that the Mediterranean diet is associated with myoprotective effects in several components of sarcopenia and declining physical function (136). Notably, sarcopenia is one of the main conditions involved in the onset of cognitive frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses showed that adherence to a Mediterranean diet is associated with reduced risk of frailty, incident frailty, cognitive decline, mild cognitive impairment, Alzheimer's disease, and progression from mild cognitive impairment to Alzheimer's disease (131)(132)(133)(134)(135). A recent systematic review also showed that the Mediterranean diet is associated with myoprotective effects in several components of sarcopenia and declining physical function (136). Notably, sarcopenia is one of the main conditions involved in the onset of cognitive frailty.…”
Section: Discussionmentioning
confidence: 99%
“…For example, between age 40 and 80 years, total skeletal muscle mass declines by 30%-50% [2]. Multifactorial environmental and genetic factors [3] (e.g., low grade chronic inflammation, hormonal changes, oxidative stress, inactivity, diet, age-related chronic diseases) are likely to be implicated in the pathogenesis of sarcopenia [4]. Sarcopenia is highly prevalent in the general population with its prevalence among people aged ≥60 years estimated to be around 10% [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a review by Granic et al [142] reiterated the beneficial effects of the Mediterranean diet towards the reduction of strength and muscle mass and towards the reduction of walking speed. Nevertheless, the authors suggest the need to harmonize methods for defining dietary models (i.e., Mediterranean diet vs.…”
Section: Author and Year Of Publication Study Design Sample Size Muscmentioning
confidence: 99%